2022
DOI: 10.1101/2022.12.29.22284028
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Untargeted serum metabolomics reveals novel metabolite associations and disruptions in amino acid and lipid metabolism in Parkinson’s disease

Abstract: Objectives: Recent advances in high-resolution metabolomics platforms allow the simultaneous measurement of thousands of small molecules produced from metabolism (metabolites), providing a map of disease-related perturbations across interconnected pathways. We used high performance, untargeted metabolomics to identify metabolic disturbances and molecular events associated with Parkinson's disease (PD) in two population-based studies. Methods: We performed a metabolome-wide association study (MWAS) on PD, using… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 39 publications
1
7
1
Order By: Relevance
“…Further comparisons between all RBD groups versus control (Figure 2B and D, Table S4) and PD_Only group by generalized fold changes and Wilcoxon rank-sum tests (Figure 2C and E, Table S5) revealed RBD-specific enriched metabolites, including secondary bile acids (lithocholate sulfate, glycolithocholate), p-cresol sulfate, and phenylacetylglutamine (PAG), which are of gut microbial origin (10), Conversely, enriched metabolites in PD_Only included glucose and cortisol, while caffeine levels were decreased. Although previous studies have reported increased plasma levels of microbial p-cresol sulfate and PAG in PD (14,16), we did not observe these in our PD_Only group but found them in the PD_RBD+ group, supporting the importance of considering PD subtypes for accurate metabolite profiling. Reductions in caffeine metabolites, including caffeine, theobromine, and 1-methylurate, were consistent features of PD, aligning with other studies (14,(26)(27)(28).…”
Section: Plasma Metabolic Features Of Pd Subtypes Focusing On Rbdcontrasting
confidence: 97%
See 2 more Smart Citations
“…Further comparisons between all RBD groups versus control (Figure 2B and D, Table S4) and PD_Only group by generalized fold changes and Wilcoxon rank-sum tests (Figure 2C and E, Table S5) revealed RBD-specific enriched metabolites, including secondary bile acids (lithocholate sulfate, glycolithocholate), p-cresol sulfate, and phenylacetylglutamine (PAG), which are of gut microbial origin (10), Conversely, enriched metabolites in PD_Only included glucose and cortisol, while caffeine levels were decreased. Although previous studies have reported increased plasma levels of microbial p-cresol sulfate and PAG in PD (14,16), we did not observe these in our PD_Only group but found them in the PD_RBD+ group, supporting the importance of considering PD subtypes for accurate metabolite profiling. Reductions in caffeine metabolites, including caffeine, theobromine, and 1-methylurate, were consistent features of PD, aligning with other studies (14,(26)(27)(28).…”
Section: Plasma Metabolic Features Of Pd Subtypes Focusing On Rbdcontrasting
confidence: 97%
“…On the other hand, 4-ethylphenylsulfate (4-EPS), a microbiota-derived metabolite found at increased levels in the plasma of individuals with autism spectrum disorder, has been shown to induce anxiety-like behaviors in mice when derived from the gut and crossing the blood-brain barrier (5860), although its impact in RBD and PD has not been investigated. p-cresol sulfate, another metabolite with a microbial origin, has been detected at higher concentrations in PD across different cohorts (14, 16). p-cresol sulfate is known to accumulate with aging and influence oxidative stress and inflammation, which may play a role in behavior disorders and neurodegeneration (61).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As pantothenic acid levels cannot be determined in vivo in the brain with current methods, investigations of peripheral levels, such as in the CSF or plasma, would be necessary to determine the temporality of alterations; this, however, would only be possible in the event that cerebral pantothenic acid changes are reflected in the periphery. There is some evidence that this may be the case, as has been observed in some studies on PD plasma and serum [27,28]; however, this has yet to be determined in DLB. As such, assessing peripheral pantothenic acid levels in a longitudinal cohort would be an intuitive and informative investigation to follow from the current study.…”
Section: Strengths and Limitationsmentioning
confidence: 89%
“…Non-CNS disturbances in pantothenic acid and related pathways have also been observed in neurodegenerative diseases; for instance, pantothenate and CoA biosynthesis has been found to be disturbed in LC-MS metabolomics analyses of PD and healthy plasma and serum samples, with decreased pantothenic acid levels observed even in the early stages of PD [27,28]. The presence of pantothenic alterations in the PD gut is disputed, with some studies showing no changes in stool sample levels [29] while others have shown decreases [30], and with another study showing positive associations between fecal pantothenic acid levels and non-motor symptoms in PD [31].…”
Section: Pantothenic Acid In Neurodegenerative Diseasementioning
confidence: 99%